CITRA PENGUASA IDEAL DALAM PERSPEKTIF POLITIK IBNU KHALDUN DAN RELEVANSINYA BAGI KEPEMIMPINAN DI INDONESIA - Mukhamad Murdiono (LPPM UNY, 2006)
This research aims at describing political thought of Ibnu Khaldun on ideal leader and its relevance to leadership in Indonesia. Through critical analysis, this research explores the formulation of types of ideal leader in Ibnu Khaldun’s thought. This is a descriptive qualitative research. The technique of data collection is documentation. The data analysis is conducted through deductive analytic technique. Inference technique through internal and external criticism is used to gain the credibility. The result of the research shows that the image of ideal leader in Khladun’s thought is like the leader described in letter of Thahir bin Husin addressed to his son, Abdullah bin Thahir after he was noted as a governor. The description consists of: a leader must be aware that God keep watching him, government must be smoothly but firmly carried out with justice, an ideal leader must concern on five day prayers as they are manifestation of life and view of life, a leader should treat his job as God’s mandate, always obey Him, spend all expenses for the sake of the people’s wealth, work hard and the result is used for the people, informative and good networking, easy to meet by people, and the primary concern of a leader must be on the people. This description is still relevant to consider in selecting Indonesia leaders.